The aggravating circumstance of gender discrimination as a response to criminal limitations on gender violence - López de Zubiría Díaz, Sandra (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
With the incorporation of “gender” as a discriminatory motive in the aggravating circumstance of art. 22.4 Criminal Code, a change in the criminal policy developed up to that time took place. Thus, the specific aggravations are complemented with a generic aggravating circumstance which, although it responds to the demands made by broad sectors, it also encourages numerous doctrinal debates especially critical of the practical problems that could arise from this modification. This text, based on a doctrinal review, complemented by a case law analysis, aims to support the incorporation of this circumstance, rejecting that there are problems of application that make the aggravating circumstance unnecessary. On the contrary, its existence is supported, arguing that it can provide a response to the current penal constrictions, which make it impossible to see the different expressions of violence as a whole, unduly differentiating between victims according to their links with the aggressor and stimulating a reluctant lack of understanding of this violence.
Keywords: gender; aggravating gender violence; discrimination; women